ANALYSIS OF THE EFFECT OF CAR FREE DAY ON MICRO BUSINESSES IN THE KRAKSAAN SQUARE AREA, PROBOLINGGO - Aziz, Abd. (Finance : Journal of Accounting and Finance, 2023)
This study explores the impact of the Car Free Day (CFD) program on the performance and sustainability of micro businesses operating in the Kraksaan Square area, Probolinggo. The CFD policy, which restricts motorized vehicle access in designated urban areas during specific hours, offers both opportunities and challenges for local entrepreneurs. Using a qualitative descriptive approach, this research involved interviews with micro business owners, field observations, and documentation studies to identify how CFD activities affect sales volume, consumer behavior, and business dynamics. The findings reveal that CFD has a positive influence on micro businesses, especially those engaged in culinary and fashion sectors, due to increased pedestrian traffic and more accessible public space. However, the success of these businesses during CFD also depends on their ability to adapt marketing strategies, product displays, and service quality. The study concludes that Car Free Day serves as a strategic opportunity for the economic empowerment of micro enterprises, provided it is supported by effective local government coordination and sustainable business practices. This research contributes to a broader understanding of urban space utilization and local economic development in the context of environmentally conscious policies.